Has India Shifted its Diplomacy toward Nepal? Analyzing Post-Blockade Relations - Pant, Bhuwaneswor (BMC Research Journal, 2025)
This paper examines how India and Nepal's diplomatic relationship has changed, especially in the aftermath of the 2015 blockade that negatively affected the two countries' relations. This paper critically investigates whether India's diplomatic efforts following the blockade represent a fundamental change in strategy or are merely a response to China's increasing might. The study explores important issues about the nature of India's diplomatic relations with Nepal using qualitative approaches, such as thematic analysis of primary and secondary data sources. In light of Nepal's expanding ties with China, this paper analyzes India's diplomatic change towards Nepal after the 2015 blockade, emphasizing its strategic adaptation to maintain regional supremacy. The study argues that India used economic incentives and diplomatic engagement to improve bilateral ties as part of its shift from a coercive to a "soft balancing" strategy. The convergence of neorealism and soft power in forming India-Nepal relations is highlighted in this paper, underscoring the necessity of ongoing communication to negotiate regional power dynamics successfully.